2012
DOI: 10.1002/ptr.3716
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effectiveness of St John's Wort Herb as an Antimicrobial Agent against Mycobacteria

Abstract: A persistent need exists for effective treatment agents for mycobacterial infections. This research investigated the effectiveness of the Hypericum perforatum herb (commonly known as St John's wort; SJW) in its growth inhibition of mycobacteria. A SJW extract was effective at inhibiting five nonpathogenic Mycobacterium isolates and Bacillus subtilis, but not Escherichia coli. Quantitative studies of concentration sensitivity to the SJW extract were performed with minimal bactericidal concentrations (MBC) rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(48 reference statements)
0
4
0
1
Order By: Relevance
“…SEM protocols were used as mentioned in [56]. Briefly, secreting and non-secreting strains were grown up overnight and fixed onto glass cover slips.…”
Section: Methodsmentioning
confidence: 99%
“…SEM protocols were used as mentioned in [56]. Briefly, secreting and non-secreting strains were grown up overnight and fixed onto glass cover slips.…”
Section: Methodsmentioning
confidence: 99%
“…The exact composition of oils and creams does, however, not seem to be very critical [10], and activity against gram-positive bacteria was even reported for hydrous SJW teas [27]. A comparison of SJW extract with its purified fractions containing hyperforin, hypericin, and pseudohypericin revealed that the extract inhibited growth of mycobacteria more effectively than the isolated components, indicating synergistic effects [28]. According to Peeva-Naumovska et al [29] a lipophilic Hypericum ointment for vaginal application was active against a number of bacteria but not Lactobacillus acidophilus which is part of the natural vaginal flora.…”
Section: Hydrophilicmentioning
confidence: 99%
“…We then determined the MBCs of LML with susceptible bacteria, four isolates of L. monocytogenes and three isolates of Mycobacterium. Scanning electron microscopy (SEM) was also conducted to identify changes in the cell surfaces after LML treatment (7).…”
mentioning
confidence: 99%